1979
DOI: 10.1042/bj1810193
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the onset of deoxyribonucleic acid synthesis during wheat embryo germination. Study of the changes in DNA polymerases A, B and C and the pool of DNA precursors

Abstract: DNA synthesis starts about 12 h after water imbibition in wheat embryos. We have determined that noticeable amounts of labelled thymidine are found inside the embryo only after 6 hr of germination. DNA polymerase C from ungerminated wheat embryos decreased markedly in activity during the first hours of germination, whereas the activities of DNA polymerases A and B increased, having a maximum at about 15 h or germination. Serological evidence has suggested a clear antigenic relationship between DNA polymerases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…Our results agree with those obtained on other monocots; in wheat embryos, DNA synthesis increases at 12 h after water imbibition [ 6 ] as well as in maize [ 12 , 24 ] with a concomitant rise in TK activity [ 7 ]. We found that during germination of maize the NSPT activity also can be detected but did not vary during the imbibition as TK1 activity, thus highlighting the role of TK1 in providing dTPP for DNA synthesis at these early stages.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results agree with those obtained on other monocots; in wheat embryos, DNA synthesis increases at 12 h after water imbibition [ 6 ] as well as in maize [ 12 , 24 ] with a concomitant rise in TK activity [ 7 ]. We found that during germination of maize the NSPT activity also can be detected but did not vary during the imbibition as TK1 activity, thus highlighting the role of TK1 in providing dTPP for DNA synthesis at these early stages.…”
Section: Discussionsupporting
confidence: 92%
“…Our results agree with those obtained on other monocots; in wheat embryos, DNA synthesis increases at 12 h after water imbibition [6] as well as in maize [12,24] with a concomitant rise in TK Figure 6. Expression of ZmTK1 in Arabidopsis TK1 double mutant allows the plants to develop in presence of CIP.…”
Section: Zmtk1 Activity Is Detected At the Onset Of Germination And Tsupporting
confidence: 92%
See 1 more Smart Citation
“…Wheat enzyme B has a 3'and 5'-exonuclease activity, as well as a 'proof-reading' capacity. This kind of activity is not shown by enzymes A and C. The latter two enzymes seem to be antigenically related, as is shown in the following paper (Castroviejo et al, 1979). Another interesting similarity with the yeast enzyme is that the enzyme having exonuclease activity in yeast is not able to use synthetic RNA primers for DNA synthesis.…”
Section: Discussionmentioning
confidence: 68%